Radiological Features of a Fibro-Osseous Pseudotumor in the Digit: A Case Report - Kwak, Min Jee; Kim, Sun Ki; Lee, Sang-Uk; Jun, Sun-Young; Lee, An hi (Journal of the Korean Society of Radiology, 2015)
A fibro-osseous pseudotumor is a rare ossifying soft tissue lesion, which is thought to be a reactive rather than a neoplastic lesion, developing due to repeated trauma. The lesion mostly occurs in the subcutaneous tissue of the proximal phalanx of the digit and predominantly affects young adults, with a slight predominance in females. The clinicopathological features can mimic those of malignant soft tissue lesions, and diagnosis can be difficult. Less is known about the radiological appearance of the lesion, including magnetic resonance imaging (MRI) features, than about histological signs. Here, we report radiological findings, including MRI features, of a fibro-osseous pseudotumor of the digit in a young female. KCI Citation Count: 0